2011
DOI: 10.5120/2966-3964
|View full text |Cite
|
Sign up to set email alerts
|

Link Load Prediction using Support Vector Regression and Optimization

Abstract: Prediction techniques are an interesting challenge in many areas like weather, banking, and finance, healthcare and so on. They are also becoming a popular subject in networking domain. This topic explores link load prediction of a network using Support Vector Regression and Optimization techniques. Support Vector Regression(SVR) is robust to outliers and can be used to online and adaptive learning.SVR has been used in other problems of networking like TCP throughput prediction, latency prediction and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, a delay is assumed to be minimised. It has been reported that the parameters of SVR, that is epsilon (e), cost or error penalty (C) and the kernel type influence prediction performance (Priyadarshini et al, 2011;Ustuner et al, 2015). Additionally, the sensitivity index can be used to determine the degree to which the independent variables impact the dependent variable (Hamby, 1994).…”
Section: Model Development and Performancementioning
confidence: 99%
“…Therefore, a delay is assumed to be minimised. It has been reported that the parameters of SVR, that is epsilon (e), cost or error penalty (C) and the kernel type influence prediction performance (Priyadarshini et al, 2011;Ustuner et al, 2015). Additionally, the sensitivity index can be used to determine the degree to which the independent variables impact the dependent variable (Hamby, 1994).…”
Section: Model Development and Performancementioning
confidence: 99%
“…The model generated by SVR only depends on a subset of the training data because the cost function for building the model ignores the training data that is close to the model prediction. SVR has been successfully applied in various fields such as bioinformatics, engineering and financial research [36].…”
Section: Support Vector Regression(svr)mentioning
confidence: 99%